The power of display: exhibition cultures and exhibited cultures in Ireland 1973-1991 - SANCHEZ-MIGALLON CANO, FERNANDO (Trinity College Dublin. School of Histories & Humanities. Discipline of History Of Art, 2020)
This research project presents a methodological and theoretical framework for conducting research on the knowledge-making capacity of museum displays in Ireland. As active agents in the production of knowledge, museum displays have been increasingly accepted as documents of significance to the evolution of ideas. In order to investigate how exhibitions create knowledge, a detailed outline of the key attributes involved in creating meaning in exhibitions will be offered. Building on research in exhibition analysis and the history of display and representation in Ireland, this research will emphasise how there is a complex network of factors that warrant consideration when assessing the epistemological function of museums in Ireland. To achieve its aims and objectives, this research project will develop a number of case studies using exhibitions as the primary site or unit of exchange in the political economy of art and art history for the production and dissemination of knowledge by adopting Du Gay et al 'Circuit of Culture' model of communication as the analytical vehicle presenting exhibitions as textual' entities in order to clarify how exhibited culture, what museums put on display, and exhibition culture, the ideas, values, and symbols that permeate and shape the practice of exhibiting, interact. Based on these principles, the aim of this research project is to formulate terms and questions that can be applied both to exhibited culture and to exhibition culture such as: how and why is it that museums select and arrange artefacts, shape knowledge, and construct a view? What is this view and how does it articulate with wider social perspectives? How do museums produce values? How does this change? And how do active audiences make meaning from what they experience in museums? The date range will offer the opportunity of contextualising these questions in relation to fundamental changes in the creation of cultural policy and cultural practice in Ireland from the influence of European cultural strategies as a result of Ireland joining the European Union and the introduction of the Arts Act in Ireland in 1973. This period also marked the beginning of the widespread re-examination of the role of museums within society during the 1970s, to the challenges presented by the globalist aspect of art and the cultural collisions in Irish life during the 1990s: between the local and global, between traditional and modern, between Catholic and secular, and between rural and urban. This research project intends to position itself at the intersection of theory and practices, also offering a much-needed critical attention and analysis to a subject that has been largely overlooked from an Irish perspective as well as posing a model of analysis where research results could be transferred and contextualised as part of the variety of relationships between the cultural industries and the creation of cultural identity.
APPROVED
Keywords: exhibition history; museology; exhibitions; museums